Professio iuris in question - Blanco-Morales Limones, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The relationships between European Union Law and pre-existing conventional law (art. 351 TFEU and art. 75 Regulation 650/2012) require going up to the principles and foundations of the rules since, in short, those of Private international law, and in particular the conflict rules, of the EU, established in art. 81 TFEU, must comply with the objectives and policies of the Union set out in art. 3 TEU, which support the delegation of -limited- powers from the Member States to the EU. To serve as a guarantee for these policies, the solutions must respond to common and coordinated principles. To affirm that the power to designate the law of nationality to govern one’s own succession is not a principle informing the Regulation is to ignore the function played by the principle of autonomy of will as a structural principle of European private international law. A guiding principle of the different instruments that articulate civil judicial cooperation, although with conditions and limits that may differ, but the principle is the same.
Keywords: Private autonomy; choice of Law; Professio iuris; Principles of European private international law; relationships between European Union Law and conventional law